FARMASI PLASMA - Gita Cahya Eka Darma (Jurnal Ilmiah Farmasi Farmasyifa, 2022)
In the last decade, the world has recognized the existence of a new branch of science in the field of medicine that uses plasma technology in the process, namely plasma medicine. A science that examines plasma as a drug in the form of a medical device or method in medical technology. The use of the term plasma medicine into Indonesian is one of the objectives of this study, because if it is translated into "plasma medicine". This study intends to provide an explanation of plasma (physics), plasma medicine and then an approach to the term into Indonesian becomes Plasma Pharmacy. The results of studies that have been carried out on researches in this new branch of science show similarities to the scope of the pharmaceutical field. Plasma pharmacy refers to the use of plasma that is applied to one or all of the stages in the manufacture of drugs (including drug raw materials, namely active ingredients, additives and packaging), functional food and cosmetics, in addition to plasma itself acting as a drug in the form of a medical device. So that the term plasma pharmacy can be used as an Indonesian vocabulary in explaining plasma medicine